Analisis Penerapan Pembelajaran Berbasis Higher Order Thinking Skills (HOTS) di SDIT Student One Islamic School - Mardhiyah, Salma; Sholehuddin, Sholehuddin (Science and Education Journal (SICEDU), 2024)
The purpose of the research is to find out how the process of implementing Higher Order Thinking Skills (HOTS)-based learning and the factors that influence the implementation of Higher Order Thinking Skills (HOTS)-based learning. The subjects in this study were seven teachers consisting of six class teachers and one subject teacher. The research method used is qualitative research method with data collection through interviews, observations and documentation studies. Data analysis used thematic analysis. The results of the data obtained show that the application of Higher Order Thinking Skills (HOTS)-based learning at SDIT Student One Islamic School includes five stages, namely analyzing SKL/KI/KD, determining learning models and determining learning strategies, facilitating students' thinking processes, formulating lesson plans, determining learning assessment and evaluation. Factors that influence HOTS learning at SDIT Student One Islamic School consist of supporting and inhibiting factors.